Management of patients with immune thrombocytopenia in the Moscow region - S. G. Zakharov; T. A. Mitina; R. V. Vardanyan; I. N. Kontievskiy; A. P. Faenko; Z. R. Tekeeva (Онкогематология, 2022)
Background. Idiopathic thrombocytopenic purpura (ITp) is an autoimmune disease characterized by antibody-mediated platelets destruction and impairment of their production, which manifests itself as: isolated thrombocytopenia, risk of spontaneous hemorrhage and bleeding of varying severity. ITp is a hematological, orphan disease with an incidence of 1–4 cases per 100,000 population. In modern literature, primary and secondary immune thrombocytopenias are distinguished. primary immune thrombocytopenia is a diagnosis of exclusion. To verify it, a certain diagnostic search is required.Aim. To evaluate clinical characteristics and treatment efficacy in patients with a confirmed primary immune thrombocytopenia in the Moscow region.Materials and methods. This article presents the results of an analysis of more than 2,400 outpatient records of patients diagnosed with thrombocytopenia (for the period from 2010 to 2022). Of these, about 400 confirmed clinical cases of various ITp forms were included in the ITp registry of the Moscow Region. All patients live in the Moscow region, receive treatment and are observed at the Center for Orphan diseases of the M.f. vladimirskiy Moscow Regional Research Clinical Institute.Results. There are 415 patients with a verified diagnosis of ITp in the register of the Moscow Region Center for Orphan diseases of the M.f. vladimirskiy Moscow Regional Research Clinical Institute (71 % (n = 294) are female). In 69.8 % (n = 290) of patients at the time of disease manifestation, hemorrhagic syndrome was recorded. As a first-line therapy, 92.8 % (n = 385) of patients received corticosteroids (prednisolone, methylprednisolone, dexamethasone), in the second-line therapy, 82 % (n = 340) of patients were recommended therapy with thrombopoietin receptor agonists (romiplostim, eltrombopag). The options for third-line therapy in patients with ITp are rituximab monotherapy, splenectomy, and intravenous immunoglobulin. Splenectomy was performed in 3.37 % (n = 14) of patients.Conclusion. when evaluating this register, the highest efficiency of thrombopoietin receptor agonists (romiplostim, eltrombopag) is observed – 84.1 % of the objective response.